Improving Children's Education through the Tutoring Program at Sentul Malaysia Kuala Lumpur Tutoring Studio - Nabila Fitriyani; Yasir Sidiq; Ganno Tribuana Aji; Muhammad Nizar; Muhammad Samsuri; Sri Sat Titi Hamranani (International Conference on Education for All, 2023)
Education is something very important that needs to be guided for children. Learning guidance strongly supports the crucial development of children's learning because it is not only available within the school system. The existence of this learning guidance program can enhance quality educational services for children. In education, students are encouraged to learn through various methods. This activity is more relaxed compared to other forms of education. All students are not forced to memorize only but they must understand and be interested in what we teach because learning is more enjoyable when using interactive methods. Educational services can also be interpreted as educational services. The word "service" itself has several meanings, ranging from personal services to services as a form of learning outside of school, which has a significant impact on students' motivation to learn. Therefore, the implementation of learning through a play-based approach is applied to motivate students in their learning journey, making them more creative and active thinkers, capable of solving problems. The Community Service Program (KKN/KI) has been successfully carried out, starting with an observation of the community center, program planning, consultation with the program implementers, and the execution of the program. The KKN/KI program includes teaching practice and implementation. The results obtained from this program include improving the active and engaging learning process, as well as enhancing students' skills in the learning process. The KKN/KI program also serves as a platform for training and learning for students, contributing to their respective universities where they are enrolled in this activity.